The Effect of Play Therapy on Children's Anxiety Level Age 4-6 years During Hospitalization at the Kronjo Health Center - Hikmah Nanda Putri; Mizwar Taufiq Firmansyah; Antonius Rino Vanchapo; Emanuel Suban Bala Lewar; Juandri Seprianto Tusi (Yayasan Adra Karima Hubbi, 2023)
Anxiety is an emotional state characterized by consistent fear, tense mood, unstable state of mind, and increased blood pressure and body chemistry. This includes the cognitive perception of the behavioral, physical and social aspects of the emotion. Anxiety makes children uncooperative and creates difficulties in carrying out treatment. Usually children are more anxious during the waiting period before treatment and this time can be used for behavior management to minimize anxiety. Children's distraction provides an effective relaxing experience during painful treatment. Cognitive behavioral therapy (CBT) is a form of active distraction, in which children are encouraged to engage in activities that calm them from anxiety. Passive distraction includes audiovisual (AV) distraction, in which children remain still and engage in visual and auditory scenes. The aim of writing several systematic reviews is to compare the provision of image recognition play therapy in children aged 4-6 years. As a comparison or comparison is without play therapy. The outcome or outcome that is measured is anxiety. Articles were searched through the database from 2019 - 2020. Searches were obtained from the PUBMED database. The keywords used are “Play Therapy And Anxiety” or “Cognitive Behavioral Play Therapy (CBT) and Anxiety” Free full text in English or Indonesian. The subjects used were children aged 4-6 years. The research design was a randomized controlled trial. Based on the results of the study that the application of therapeutic games to children who are hospitalized reduces preoperative anxiety and can reduce postoperative pain, improve behavior and attitudes, and reduce anxiety during a hospital stay. Conclusion: play therapy has a beneficial impact on the care of hospitalized children and should be implemented in pediatric units after assessing the resources and training required for pediatric nurses.